UNIT 6.35 Quantification of Th1 and Th17 Cells with Intracellular Staining Following PMA/Ionomycin Stimulation. Issue 1 (5th January 2015) - Karlsson, Fridrik; Hassan‐Zahraee, Mina
Abstract : Cytokine‐producing cells are at the center of the adaptive immune responses, and quantifying these cells is an important aspect to build understanding of the immune response. In particular, Th1 and Th17 cells have been implicated in the pathogenesis of such diseases as inflammatory bowel disease, rheumatoid arthritis, and multiple sclerosis. Quantification of Th1 and Th17 cells can provide important information in research of these diseases and other Th1‐ and Th17‐mediated immune disorders. In vitro stimulation of cells followed by surface and intracellular staining, presented here, has the advantage of detecting the cytokines directly instead of relying exclusively on surrogate surface markers which, although showing enrichment for the effector T cells, are not specific markers for the cytokine‐producing cells. © 2015 by John Wiley & Sons, Inc.